Rare Infantile Inguinal Hernia Containing Uterus, Fallopian Tubes and Ovaries - Al-Bahlooli, Saeed H.; Mehras, Amattalkhaleq O.; Bahakim, Kamal O.; Al-Selwi, Abdulhakim A. (Thamar University Journal of Natural & Applied Sciences, 2023)
The presence of ovaries and fallopian tubes in the sac of female inguinal hernia is rare especially in childhood. However; complete herniation of the uterus side by side with ovaries and tubes constitutes extreme rarity. We herein present a 6-years old female patient whose inguinal hernia contains uterus in addition to ovaries and fallopian tubes. The aim of this report is to attract attention of the surgeons to this rare possibility during surgical management of hernia in order to avoid the likely damage to herniated structures.